The necessity of a non-linear & non-stationary data processing in engineering and the new Hilbert Huang Transform (HHT) - Raja, J.E.; Loo, C.K.; Rao, M.V.C. (2007)
Data analysis is indispensable for engineering, for data is the only link between the theory and the reality. Traditional data analysis methods such as Fourier analysis are all based on linear and stationary assumptions i.e. the signal to be processed must be linear and temporally stationary; otherwise, the resulting Fourier spectrum will make little physical sense. Practical signals such as speech, machine vibrations, biomedical measurement and communications most likely to be both nonlinear and non-stationary. Hence new methods are needed to analyze the data from nonlinear and non-stationary process. Hilbert-Huang Transform(HHT) is a new data processing technology developed by NASA Goddard Space Flight Center. The HHT is derived from the principles of empirical mode decomposition (EMD) and the Hilbert Transform. This paper presents the suitability of using HHT for nonlinear and non-stationary data analysis. The efficiency of the new method is tested on a set of vibration data collected from Westland helicopter gearbox, a non-linear and non-stationary system. Both simulation and the experimental results indicate that this new method HHT is more suitable for non-linear and non-stationary process.